Association between maternal erythrocyte polyunsaturated fatty acid levels during pregnancy and offspring weight status: A birth cohort study - Wu, Shengchi; Zhao, Feng; He, Yannan; He, Tingchao; Duan, Sufang; Feng, Gang; Chen, Yujing; Wang, Xin; Szeto, Ignatius Man-Yau; Lin, Lizi; Cai, Li (Frontiers in Nutrition, 2022)
Background: The findings of the association between maternal polyunsaturated fatty acid (PUFA) levels during pregnancy and offspring weight status are controversial. Furthermore, few studies have focused on Asian populations or used erythrocyte membranes as biological markers. We aimed to examine the associations between maternal erythrocyte PUFA and offspring weight status within the first 2 years among Chinese population. Methods: A total of 607 mother-child pairs were recruited from a birth cohort. Maternal erythrocyte n-3 and n-6 PUFA during pregnancy were measured by gas chromatography, and the ratio of PUFA was calculated. Weight-, and BMI-for-age z scores were calculated for offspring at 1, 3, 6, 8, 12, 18, and 24 months of age. The risk of overweight and obesity was defined by WHO criterion. Generalized Estimating Equation (GEE) model was carried out for repeated anthropometric data within 2 years of age. Results: Maternal erythrocyte docosapentaenoic acid (DPA) was inversely associated with offspring BMI-for-age z score [tertile 2 vs tertile 1, β: -0.18 (-0.29, -0.00)]. Higher maternal erythrocyte arachidonic acid (AA) was inversely associated with lower offspring weight- and BMI-for-age z score [tertile 3 vs tertile 1, β: -0.18 (-0.35, -0.02), -0.22 (-0.38, -0.06), respectively]. Furthermore, higher maternal erythrocyte AA [tertile 3 vs tertile 1, OR: 0.52 (0.36, 0.75), Ptrend<0.001], total n-6 PUFA [tertile 3 vs tertile 1, OR: 0.56 (0.39, 0.81), Ptrend=0.002] were all associated with decreased risk of overweight and obesity in offspring. Maternal erythrocyte n-6/n-3 PUFA and AA/EPA ratio were not associated with offspring weight status. Conclusions: Chinese maternal erythrocyte PUFA might influence offspring weight status within 2 years of age. Further Asian studies are still needed.